The zero of an expression is when the expression results to 0, for an input value.
[tex]x = 3[/tex] is a zero of [tex]4x^2 - 8x - 12[/tex]
Given that:
[tex]f(x) = 4x^2 - 8x - 12[/tex]
[tex]x = 3[/tex]
Substitute 3 for x
[tex]f(3) = 4 \times 3^2 - 8 \times 3 - 12[/tex]
Simplify
[tex]f(3) = 36 - 24 - 12[/tex]
[tex]f(3) = 0[/tex]
When 3 is substituted for x, the quadratic expression [tex]4x^2 - 8x - 12[/tex] have a value of 0
Hence, [tex]x = 3[/tex] is a zero of the quadratic expression.
Read more about zero of expressions at:
https://brainly.com/question/19525535